(untitled) (Bangladesh Heart Journal, 2024)
Objective: Acute myocardial infarction is one of the leading causes of all acute emergencies and is becoming an important public health problem in the developing countries. Non-ST elevation myocardial infarction (NSTEMI) is more heterogeneous in their presentation and may be poorly characterized in clinical practice, leading to greater variation in diagnosis and treatment. Patients with diabetes and hypertension who develop a NSTEMI are at increased risk for poor hospital outcome. This study is aimed to assess the differences between hypertensive diabetic and hypertensive non-diabetic patients with NSTEMI and to evaluate the prognostic impact of selected clinical and laboratory parameters on the occurrence of hospital complications. Methods: This was a cross-sectional analytical study. All the adult hypertensive patients of newly diagnosed NSTEMI with or without diabetes mellitus admitted in Ibrahim Cardiac Hospital & Research Institute, Dhaka who fulfilled the inclusion and exclusion criteria were enrolled. The study population comprised of 100 hypertensive patients with their first NSTEMI, and were divided into two groups according to the presence of type 2 diabetes mellitus. Group I (n = 40) patients were diabetic and Group II (n = 60) were non-diabetic. Hospital outcome of the study population was recorded. The incidence of in hospital adverse clinical events in the two groups was compared by using the odds ratio of the two binomial proportion analyses. Results: Among 100 hypertensive NSTEMI patients, 40% were diabetic (Group I) and 60% were non-diabetic (Group II). Mean age was 58.1±10.2 years in case of diabetic group (Group I) and 56.3±10.5 years in non-diabetic group (Group II) ranging from 30-70 years. Male patients (66%) were predominant in the study. Most common clinical presentation was chest pain which was 77.5% in Group I and 83.3 % in Group II followed by sweating (12.5% and 16.7%), dyspnea (10.0% and 11.7%), syncope (5.0% and 6.7%) and atypical chest pain (2.5% and 3.3%) respectively. Smoking was the commonest risk factor which was 62.5% in Group I and 75% in Group II followed by dyslipidemia (32.5% and 36.7%), family history of IHD (30% and 23.3%) and obesity (22.5% and 13.3%) respectively. Diabetic hypertensive patients had significantly higher heart rate, hypertensive peaks and more episodes of asymptomatic ST segment depression. Most common in hospital complications were heart failure (30% and 16.7%), arrhythmias (22.5% and 6.7%), renal failure (10% and 5.0%), cerebral ischemia (7.5% and 1.7%), death (7.5% and 3.3%) and cardiogenic shock (5.0% and 3.3%) in Group I and Group II respectively. Conclusion: In hospitals, adverse clinical events were more frequent in diabetic hypertensive individuals compared to non-diabetics. Bangladesh Heart Journal 2024; 39(1): 17-23